2006
DOI: 10.1093/ajcn.83.3.657
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, placebo-controlled, calcium supplementation study in pregnant Gambian women: effects on breast-milk calcium concentrations and infant birth weight, growth, and bone mineral accretion in the first year of life

Abstract: Calcium supplementation of pregnant Gambian women had no significant benefit for breast-milk calcium concentrations or infant birth weight, growth, or bone mineral status in the first year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
4
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(183 citation statements)
references
References 39 publications
6
169
4
4
Order By: Relevance
“…Low calcium intake does not reduce breast milk calcium, nor does it lead to increased resorption of the maternal skeleton during lactation (440, 535, 728 -731). Conversely, high calcium intake similarly fails to increase breast milk calcium or reduce skeletal resorption during lactation (206,275,440,452,484,535,723,729,730); its only effect may be to increase urinary calcium excretion. These data from randomized clinical trials and cohort studies indicate that it does not matter how much calcium is consumed during lactation because maternal skeletal resorption is hormonally programmed to supply needed calcium.…”
Section: Human Datamentioning
confidence: 99%
“…Low calcium intake does not reduce breast milk calcium, nor does it lead to increased resorption of the maternal skeleton during lactation (440, 535, 728 -731). Conversely, high calcium intake similarly fails to increase breast milk calcium or reduce skeletal resorption during lactation (206,275,440,452,484,535,723,729,730); its only effect may be to increase urinary calcium excretion. These data from randomized clinical trials and cohort studies indicate that it does not matter how much calcium is consumed during lactation because maternal skeletal resorption is hormonally programmed to supply needed calcium.…”
Section: Human Datamentioning
confidence: 99%
“…Calcium supplementation studies in pregnancy have not had congenital or neonatal rickets as an outcome, but 3 RCTs of maternal calcium supplementation during pregnancy measured neonatal bone [165][166][167] . These RCTs were conducted in West Africa where typical dietary calcium intakes are 250-300 mg/day [165] , in the United States with an average intake of about 2,000 mg/ day [166] , and in a multicenter World Health Organization study in populations with dietary calcium intake of approximately 600 mg/day (Argentina, Peru, India, Egypt, Vietnam, South Africa) [167] .…”
Section: Evidencementioning
confidence: 99%
“…However, Ca supplementation studies of women during lactation (83,152) , and more recently during pregnancy (24) , have demonstrated that breast-milk Ca concentration is independent of maternal Ca intake, even amongst women with very low Ca intakes. In addition, because breast-milk Ca secretion is regulated by the casein, phosphate and citrate components, it is now recognised that maternal Ca intake is unlikely to influence breast-milk Ca secretion directly (173) .…”
Section: Influence On the Mother In Lactationmentioning
confidence: 99%